Konflik Pertanahan Di Blok Bleberan Dan Kalen Rembet (Studi Kasus Konflik Antara Perhutani Kph Balapulang Dan Masyarakat Desa Songgom Kecamatan Songgom Kabupaten Brebes) - Fikri, Fito Akhsanul; Ngabiyanto, Ngabiyanto; Isdaryanto, Noorochmat (Unnes Political Science Journal, 2017)
The problems in this research are: (1) what are the factors that led to conflicts between Perhutani KPH Balapulang Songgom Village Society?, and (2) how the efforts undertaken Perhutani KPH Balapulang and Rural Community Songgom in resolving the conflict over land ?. The purpose of this study are: (1) determine the factors that led to conflicts between Perhutani KPH Balapulang and Songgom Village Society, (2) know the efforts made Perhutani KPH Balapulang and Rural Community Songgom in resolving the land conflicts. The method in this study used qualitative research methods. Data collection techniques using interviews, observation and documentation. These results indicate that there are several factors that cause conflict between Perhutani KPH Balapulang and Society Songgom namely: misuse of the seizure of land and property rights to land. Then in resolving the conflict made several attempts namely, socialization, mediation and last through the courts. Suggestions researcher for the parties involved kooflik that Perhutani KPH Balapulang and village communities Songgom suggested dissemination of the use rights over the land, or the status of the land, so that people understand the status of the land by Perhutani suggested for more to be improved, should Perhutani provide guidance to the public to plant ground with plant stands minimizing the occurrence of a disaster that causes a lack of catchment areas, should sharecropper and community awareness to safeguard natural resources for survival of harmony without damaging the surrounding nature, and tenant farmers should manage land set down rules perhutani, should mananami land in accordance with the command of the central government and not by planting plants with plants that have economic value to the exclusion of the benefits of the land as catchment areas.